Role Of Financial Intermediaries in Shadow Schemes: Risk-Based Approach - Inna Tiutiunyk; Yuliia Humenna (Financial Markets, Institutions and Risks)
The article is devoted to the study of the role of financial intermediaries in the shadow sector of the economy. The main purpose of the article is to analyze and systematize the work of scientists to assess the risk of shadow transactions with the participation of financial intermediaries. The results of the analysis of scientific publications on these issues show a wide variety of approaches to the study of these problems. Significant differences in the functioning of the financial, banking, insurance and investment markets of different countries have led to the need to develop and implement their own methodologies for assessing the risk of participation of financial intermediaries in shadow transactions at the state level. The paper summarizes the methodological approaches to assessing the risk of participation of financial intermediaries in shadow transactions in some countries. The methodological tools of the analysis are the methods of analysis and synthesis, generalization and comparative analysis. The object of the study are insurance companies, banking institutions and investment funds – participants in shadow schemes of income concealment. The article summarizes the most typical schemes of income concealment in terms of individual groups of financial intermediaries. The conclusion about the dual nature of banking institutions in these operations is made: 1) banking institutions as a ‘buffer’, and sometimes a direct participant on the way to the legalization of shadow income; 2) banking institutions as a subject of primary financial monitoring and control. Insurance operations that are subject to enhanced control by regulatory authorities include: pseudo-insurance operations; concluding an insurance contract with subsequent receipt of compensation for the occurrence of a fictitious insured event; concluding an insurance contract with an inflated insurance value of the object. Based on the analysis of transactions with signs of fictitiousness, which are realized on the investment market of Ukraine, the conclusion about the important role of technical securities in operations on shadowing of incomes and their further legalization is made. The results of the study can be useful for public financial monitoring and control bodies in terms of identifying transactions that could potentially pose a threat to the formal sector of the economy and developing measures to prevent them.